2015
DOI: 10.1371/journal.pone.0132091
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of Mediterranean Hotspot Biodiversity: Re-Evaluating the 'Tertiary Relict' Hypothesis of Macaronesian Laurel Forests

Abstract: The Macaronesian laurel forests (MLF) are dominated by trees with a laurophyll habit comparable to evergreen humid forests which were scattered across Europe and the Mediterranean in the Paleogene and Neogene. Therefore, MLF are traditionally regarded as an old, 'Tertiary relict' vegetation type. Here we address the question if key taxa of the MLF are relictual. We evaluated the relict hypothesis consulting fossil data and analyses based on molecular phylogenies of 18 representative species. For molecular dati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 47 publications
4
72
0
Order By: Relevance
“…Désamoré et al., ; Franzke, Sharif Samani, Neuffer, Mummenhoff, & Hurka, ; García‐Verdugo, Mairal, Monroy, Sajeva, & Caujapé‐Castells, ; Jones, Reyes‐Betancort, Hiscock, & Carine, ; Kondraskov et al., ). Positive correlations between the geological age of a given archipelago and lineage colonization time may be therefore restricted to very few cases (Kondraskov et al., ). Rather, molecular reconstructions indicate that multiple waves of island immigrants through time, hybridization and back‐colonization are more common than initially thought (Caujapé‐Castells et al., ; Emerson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Désamoré et al., ; Franzke, Sharif Samani, Neuffer, Mummenhoff, & Hurka, ; García‐Verdugo, Mairal, Monroy, Sajeva, & Caujapé‐Castells, ; Jones, Reyes‐Betancort, Hiscock, & Carine, ; Kondraskov et al., ). Positive correlations between the geological age of a given archipelago and lineage colonization time may be therefore restricted to very few cases (Kondraskov et al., ). Rather, molecular reconstructions indicate that multiple waves of island immigrants through time, hybridization and back‐colonization are more common than initially thought (Caujapé‐Castells et al., ; Emerson, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent Bayesian divergence time dating based on ITS sequence data (Kondraskov et al. ; see also Thiv et al. ) found a cladogenetic origin in the late Pleistocene or even later for Ae.…”
Section: Discussionmentioning
confidence: 99%
“…; Kondraskov et al. ), suggesting rather recent species formation without sufficient time to differentiate from their respective ancestor and/or sister species. A recent Bayesian divergence time dating based on ITS sequence data (Kondraskov et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, an analysis on 18 representative and mainly woody laurel forest species by Kondraskov & al. () revealed that several of them might be too young to be Tertiary relicts. Concerning the number of colonization events within lineages, one colonization event or multiple colonization events to Macaronesia have been indicated (Carine & al., ; Silvertown, ; Silvertown & al., ).…”
Section: Introductionmentioning
confidence: 99%